Water column raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M167 - Walter Menapace; Debora Duarte; Miriam Römer (PANGAEA, 2025)
Raw water column data were collected aboard RV METEOR during cruise MSM167 using a Kongsberg EM 122 multibeam echosounder between 17.10.2020 and 30.10.2020 in the Alboran Sea and Gulf of Cadiz. The aim of the cruise was to investigate the mud volcanoes of the region. The EM122 system is a hull-mounted deep water MBES providing accurate bathymetric mapping down to full ocean depth. The system contains two linear transducer arrays in a Mills cross configuration with separate units for transmitting and receiving. The EM122 system used a nominal frequency of 12 kHz with a beam width configuration of 2° (TX) by 2° (RX). For beam spacing the high-density-equidistant mode was chosen, which provides 432 independent depth values (soundings) perpendicular to the track for each ping. Using the two-way-travel-time and the beam angle known for each beam, and considering the ray bending due to refraction in the water column by sound speed variations, depth and position are calculated for each beam. A combination of amplitude (for the central beams) and phase (slant beams) is used to provide a measurement accuracy practically independent of the beam pointing angle. Furthermore, the EM122 system applies the dual swath technology: instead of one ping two pings are simultaneously transmitted and recorded, one slightly tilted forward and the second backward. This enables a denser bottom coverage which allows higher survey speeds. For multibeam mapping surveys speeds of 9 to 11 knots were carried out. The Ping Mode was set to Auto, which enabled the system to use CW (continuous wave) pulses in shallow modes and FM or chirp pulses in deep modes. FM or chirp pulses transmit more energy into the water, thus enabling greater ranges of the beams leading to a better across-track coverage of the seafloor particularly at greater depth. Monitoring and quality control of the data was conducted with the Kongsberg Seafloor Information System (SIS). The software controls the sector coverage (angle, beam spacing), depth settings (swath mode, ping mode) and transmission control (pitch stabilization). The data was stored every 30 minutes as an *.wcd file. During data acquisition, sound velocity measurements were applied on the data for data calibration. For more details on data acquisition please see the M167 cruise report. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed.